2022
DOI: 10.3389/frwa.2022.818469
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeologic and Thermal Effects of Glaciations on the Intracontinental Basins in Central and Northern Europe

Abstract: We use a fully coupled hydro-thermal model (TH) to quantify changes in the pore pressure and temperature distribution following the Last Glacial Maximum (LGM) in the intracontinental basins in Central and Northern Europe. We demonstrate that even without considering a direct mechanical coupling from the visco-elastic lithosphere rebound, the system is, at present-day, in a state of hydrogeologic and thermal disequilibrium as a result of the past ice sheet dynamics. We find that the local geology exerts an addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…The situation differs in regional groundwater system, which showcases an evidence of lateral outflow beyond the model domain (Supplementary Figure 5). However, these boundary effects can be considered of secondary relevance for current study, given that the internal flow geometries within the limits of Brandenburg are not significantly affected by our choice of open vs. closed boundary conditions, and, in principle, in agreement with a flow pattern obtained from the larger-scale model of CEBS (Frick et al, 2022;Supplementary Figure 5).…”
Section: Model Limitations and Uncertaintiessupporting
confidence: 60%
See 2 more Smart Citations
“…The situation differs in regional groundwater system, which showcases an evidence of lateral outflow beyond the model domain (Supplementary Figure 5). However, these boundary effects can be considered of secondary relevance for current study, given that the internal flow geometries within the limits of Brandenburg are not significantly affected by our choice of open vs. closed boundary conditions, and, in principle, in agreement with a flow pattern obtained from the larger-scale model of CEBS (Frick et al, 2022;Supplementary Figure 5).…”
Section: Model Limitations and Uncertaintiessupporting
confidence: 60%
“…Due to the no-flow boundary along the model edge, groundwater leaves the aquifer via cross-flow to the adjacent units, eventually discharging at the surface. A larger basin model of the whole Northern Europe suggested that this deep groundwater flow actually continues north-west toward the most buried offshore parts of the NGB (Frick et al, 2022).…”
Section: Groundwater Flow: the Initial Statementioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy includes larger concentrations of aromatic humic and fulvic acids, derived from current or recent mixing with pools of surface-photosynthate delivered to these shallower systems via groundwater recharge 7 , 8 . These hydrogeologic connections can be modern, or may reflect geologic processes, as in particular, paleo-recharge from past glacial cycles has been invoked as a global mechanism for enhanced penetration of surface waters into the near subsurface, sometimes to kilometers depth 9 , 10 . Subsurface systems can also contain much older biotic input if leaching occurs from proximal kerogen/bitumen rich ore deposits, such as the case with coal beds and oil field systems 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The load of the ice sheets affected the Earth's crust and glacial isostatic adjustment (Lambeck et al, 2014), and processes such as postglacial rebound (Spada, 2017) or hydrogeological adaptations (Amberg et al, 2022;Frick et al, 2022) are still ongoing.…”
Section: Introduction and Rationalementioning
confidence: 99%